The ultra-sensitive visual biosensor based on thermostatic triple step functional nucleic acid cascade amplification for detecting Zn2+. (30th August 2019) - Li, ShuTing; Li, GuiShan; Du, ZaiHui; Zhu, LongJiao; Tian, JingJing; Luo, YunBo; Huang, KunLun; Xu, WenTao
Highlights: Ultra-sensitive biosensor was created based on thermostatic triple step functional nucleic acid cascade amplification. The visual signal output was established based on a large amount of G4 DNAzymes achieved by the HCR-SDA reaction. The system exhibited an excellent linear range within 10 pM–100 nM, and its limit of detection (LOD) was 1.075 pM. This method is universal, and the detection of multiple target substances can be achieved. Abstract: Here, we present an ultra-sensitive visual biosensor based on thermostatic triple step functional nucleic acid cascade amplification for detecting Zn 2+ . A Zn 2+ -assisted cDNAzyme assay is conducted and the Zn 2+ is successfully converted into nucleic acids to achieve the first circular amplification within 1 h. The cleavage products prompted Hybridization Chain Reaction (HCR), forming multiple DNA nanowire structures with branched chains. And the Strand Displacement Amplification (SDA) were further empowered by the HCR products with the addition of the amplification enzyme and the endonuclease. In just 80 min, the second and third-order signal amplifications are reached. With the addition of Hemin and chromogenic substrates, the visual signal output is achieved in 15 min based on the large amount of G-quadruplex (G4) DNAzymes. This biosensor can detect levels as low as 1.075 pM Zn 2+, showing a good linear range within 10 pM–100 nM. It shows considerable potential for the Zn 2+ quantitative detection.